PARAMEDIC PRACTITIONER: A SURVEY OF SCOPE OF PRACTICE AND DEVELOPMENT REQUIREMENTS. Issue 9 (18th August 2016) - Colver, Keith; Fitzpatrick, David; Cooper, Matthew; Ward, Jim
Abstract : Background: The Scottish Ambulance Service introduced paramedic practitioners in 2004 to reduce unnecessary hospital admissions. Development of the role has varied across the UK but little is known about this professional group within Scotland. Aims: To describe paramedic practitioners views on their scope of practice and identify areas for improvement. Methods: An online cross-sectional questionnaire was undertaken during July–August 2015. Participants: current staff identified as having completed paramedic practitioner training (N=64). Quantitative data are reported using descriptive statistics and qualitative data analysed using framework analysis. Results: Forty two per cent (n=27) completed the survey, of which 52% (n=14) were active practitioners. Average length of service was 19.52 years (range: 3–24 years) including 4.66 years (range: 0.83–11) within a practitioner role. Variation was reported on funding sources and educational levels (stand-alone level 9 modules to MSc). Current practice settings were described as urban (57% [n=8]), semi-rural (29% [n=4]) and rural (14% [n=2]) involving 999 response, Minor Injuries Clinics, Out of Hours and GP practices. Adult, paediatric and care of the elderly were the most common areas of practice (73%). The remaining areas consisted of: critical, palliative, mental health and other (27%). Most used skills were described as: advanced clinical assessment and medicines; least used: catheterisation, minor ailments/injuries. Skills reported as missing or requiring development were: paediatrics, palliative care and mental health. Mean ' comfort in practice ' was rated as 4.23 on a 7 point-scale ('comfortable' [1] -'very comfortable' [7]). Difficulties were reported in call-allocation and utilisation. Variation across practice settings caused difficulties with: record-keeping, inconsistent referral processes, guideline use, peer review and CPD. These created governance and role development challenges. Conclusion: Practice is inconsistent, reflecting variations in development processes and practice areas. Practitioners are comfortable in their role and would value standardisation in clinical practice guidelines, education and governance.